Antitrust Law Reform in Emerging Economies: A Comparative Study between Indonesia and Oman - Dwi Edi Wibowo; Aurea Qonita Wibowo; Souad Ahmed Ezzerouali (University of Jember, Indonesia, 2025)
This study aims to analyse anti-monopoly law reform efforts in developing countries by conducting a comparative study between Indonesia and Oman. This research is normative legal research using conceptual and legislative approaches. The research findings confirm the urgency of anti-monopoly legal reform in developing countries as an important instrument for creating a fair, competitive, and sustainably innovative market. The reform aims not only to meet international standards but also to be grounded on the principles of social justice, economic democracy, and national legal sovereignty amid global economic dynamics and digital technology. Philosophically, this reform is necessary to protect the public interest from monopolistic practices that widen economic disparities and undermine general welfare. A comparative study between Indonesia and Oman reveals differences in the context and approach to reform, with Indonesia focusing on updating laws and strengthening dispute resolution mechanisms, while Oman integrates regulations with Islamic law and economic diversification strategies. Both emphasise institutional strengthening, regulatory harmonisation, and increased awareness among business operators as key to the reform's success. The results of this comparison open opportunities for the exchange of experiences to enrich anti-monopoly legal reform strategies, supporting the creation of competitive and inclusive markets, as well as sustainable economic growth and the equitable distribution of community welfare in developing countries.